Total sediment thickness of the world's oceans and marginal seas, version 3 (GlobSed) - Straume, Eivind Olavson; Gaina, Carmen; Medvedev, S; Hochmuth, Katharina; Gohl, Karsten; Whittaker, Joanne; Abdul Fattah, R; Doornenbal, J C; Hopper, J R (PANGAEA, 2025)
NCEI's global ocean sediment thickness grid of Divins (2003) updated by Whittaker et al. (2013) has been updated again for the NE Atlantic, Arctic, Southern Ocean, and Mediterranean regions. The new global 5‐arc‐minute total sediment thickness grid, GlobSed, incorporates new data and several regional oceanic sediment thickness maps, which have been compiled and published for the, (1) NE Atlantic (Funck et al., 2017; Hopper et al., 2014), (2) Mediterranean (Molinari & Morelli, 2011), (3) Arctic (Petrov et al., 2016), (4) Weddell Sea (Huang et al., 2014), and (5) the Ross Sea, Amundsen Sea, and Bellingshausen Sea sectors off West Antarctica (Lindeque et al., 2016; Wobbe et al., 2014). This version also includes updates in the White Sea region based on the VSEGEI map of Orlov and Fedorov (2001). GlobSed covers a larger area than NCEI's previous global grids (Divins, 2003; Whittaker et al. 2013), and the new updates results in a 29.7% increase in estimated total oceanic sediment volume. This dataset has been archived in the framework of the PANGAEA US data rescue initiative 2025.
Keywords: sediment thickness